Copper and cobalt nanoparticles embedded in naturally derived graphite electrodes for the sensing of the neurotransmitter epinephrine. (29th March 2018) - Bala, Kanchan; Suriyaprakash, Jagadeesh; Singh, Prem; Chauhan, Kalpana; Villa, Alberto; Gupta, Neeraj
Abstract : Cu and Co nanoparticles on naturally derived graphitic carbon as a potential electrode for the electrochemical sensing of the neurotransmitter epinephrine. Abstract : We have demonstrated a successful technique for the preparation of metal nanoparticles supported on graphite derived from naturally abundant biomass waste. The physicochemical properties of the synthesised materials were investigated using microscopic and spectroscopic methods, and the materials were applied further for the electrochemical detection of the neurotransmitter epinephrine (EP).